Testosterone cycle and regulation of reproductive events in the lizard Phymaturus punae (Liolaemidae) from the highlands of the Andes, Argentina - Boretto, Jorgelina Mariela (2014)
The genus Phymaturus, entirely viviparous and mostly herbivorous, inhabits the cold and 25 harsh environments of the Andean highlands of Argentina and Chile, and the Patagonian 26 steppe of Argentina. Phymaturus punae is a vulnerable lizard endemic to the Biosphere 27 Reserve San Guillermo (National Park and Provincial Reserve) in San Juan (Argentina) that 28 inhabits high altitudes of 3,100 to 4,200 m. The reproductive cycles of males and females of 29 P. punae have been described previously. Males perform a prenuptial and annual cycle, and 30 females reproduce once every two years. As a consequence, the adjustment in the timing of 31 males to the reproductive cycles of females must be very precise to ensure reproductive 32 success. We elucidate the time of mating and the asynchrony of males and females 33 reproductive events in P. punae based on endocrine and ultrastructural studies. Present 34 hormonal results support the idea that copulation in P. punae occurs at the end of the activity 35 season. Ultrastructural features observed in Sertoli and Leydig cells indicate that both types of 36 cells have the potential to synthesize steroid hormones, to support the spermatogenic cycle 37 and the mating period, respectively. In P. punae the cases of temporal asynchrony in steroid 38 activity, suggest that this mechanism must be important to start the spermatogenesis in spring, 39 supported by the steroid activity of Sertoli cells, since Leydig cells are inactive. Nevertheless 40 the asynchronic steroid mechanism seems to be more necessary in Phymaturus species with 41 continuous or postnuptial cycles, than in species with prenuptial cycles, like P. punae.